The Description of Alexithymia in Nursing Students at Padjadjaran University with Social Media Addiction - Iyus Yosep; Ai Mardhiyah (STIKep PPNI Jawa Barat, 2022)
Aim: People’s inability to recognize and express their emotions (alexithymia) seems to be a risk factor in causing social media addiction, where the higher level of social media addiction, the higher level of alexithymia. This study aims to determine the prevalence of alexithymia among nursing students at Padjadjaran University who experience social media addiction. Method: This study used a quantitative descriptive design. The research samples were 216 nursing students at Padjadjaran University who experienced social media addiction after being screened using the IAT instrument, with a total sampling technique. The instrument used to see alexithymia was TAS-20 instrument. In this study, the data are analyzed by univariate analysis and presented in the form of frequency distribution tables. Result: The result of this study showed that less than half of the respondents, which were 94 (43.5%) experienced a high level of alexithymia, with alexithymia subscales average scores were 20,68 + 7.90 for DIF, DDF 16 + 5.54, and EOT 22,52 + 8.32. Conclusion: The conclusion of this study is that respondents who experienced moderate and severe social media addiction have higher alexithymia scores. Therefore, it is necessary to have preventive and promotive solutions for nursing students who don’t or have alexithymia.